Zanimivosti iz življenja lesne sove Strix aluco - Vrezec, Al (Društvo za opazovanje in proučevanje ptic Slovenije, 2015)
The author presents his observations and a thorough study of the Tawny Owl Strix aluco in the village of Hrastje near Polčane from 1991 to the beginning of 1994. The observations were made possible with the aid of the owl's recorded songs or calls broadcast there, for with such method the presence andnumber of owls can be quickly ascertained in a certain area. In this way a Tawny Owl male, among other birds, was provoked which, however, reacted ratheraggressively to the recorded song. In May 1991 the author discovered a Tawny Owl's nest in a beech hole, but unfortunately it went to ruin due to a sudden and considerable fall in temperature at that time. In the following years, however, the Tawny Owl bred there successfully In 1992, 4 chicks were fledged through the entire summer they kept together, but in late autumn theysuddenly scattered to the four winds. The author describes the bird's three dif ferent daily resting places: nest hole, man made hatchery, and chimney on the roof in the vicinity of the owl's nest hole. Most interesting was certainly the latter, for the owl was not no ticed there by other birds and thus remained undisturbed. The test, according to which the owl's song wasbroadcast in the immediate neighbourhood of the above mentioned house was interesting as well. There were a number of different birds attracted by it, but did not dis turb the owl perching on top of the chimney The studied owl was a grey variety of this species. In this region it hunts also in different sheds, stables and stalls, where it catches according to the author's belief -mostly dorm ice Glis glis, black rats Rattus rattus and house mice Mus usculus, which together with other small mammals hunted in nearby forests any vineyards represent the greater part of its die in this area. Avtor opisuje triletno opazovanje in preučevanje lesne sove Strix aluco v vasiHrastje pri Poljčanah od leta 1991 do začetka leta 1994. Avtor predstavi opazovanje sov s pomočjo predvajanja posnetka sovjega petja. S takšno metodo opazovanja je mogoče hitro ugotoviti prisotnost in številčnost sov v nekem območju. Tako je avtor izzval samca lesne sove, ki pa se je ob predvajanju posnetka vedel precej agresivno. Maja 1991 je pisec odkril leglo v duplu bukve, ki pa je zaradi podhladitve istega leta žal propadlo. Toda v naslednjihletih je tu sova še uspešno gnezdila. Leta 1992 so bili speljani štirje mladiči vse poletje so bili skupaj, jeseni in pozimi pa so se razkropili. Pisec omenja tri različna dnevna počivališča lesne sove: gnezditveno duplo, umetno valilnico in dimnik na strehi hiše blizu gnezditvenega drevesa. Najzanimivejše je prav slednje, saj ptiči sove na dimniku niso opazili in je niso napadali. Zanimiv je bil tudi poizkus, ki ga je avtor izvedel s predvajanjem sovjega oglašanja v neposredni bližini omenjene hiše. Ptiči so sicer prileteli, vendar sove na dimniku niso vznemirjali. Opazovana sova je bila siva različica lesne sove. Lesna sova na tern območju pleni tudi v različnih lopah, hlevih itd., kjer lovi po avtorjevem mnenju predvsem polhe Glis glis, črne podgane Rattus rattus in hišne miši Musmusculus, ki skupaj z drugimi malimi sesalci, ki jih sova pleni v gozdu in vinogradih, sestavljajo glavnino prehrane na tem območju.